Pengaruh Diversitas Dewan dan kinerja keuangan terhadap voluntary corporate disclosure - Aisyah, Esy Nur (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2016)
More disclosure can reduce agency costs incurred by the company. The more management (agent) reveal information about the company can reduce the conflict to shareholders (principal). Therfore, a voluntary disclosure more to minimize the occurence ofÂ  information asymmetry. The more management companies disclose information about the incentives obtained become more, because basically shareholders (principal) would be willing to pay the cost of monitoring surveillance to prevent the hazard of the agent.The aim of this study is to analyze and discribe how diversity influences gender and educational background of the board as well as the financial performance of the corporate voluntary disclosure. Definition councils in this study combines the board of commissioners and board of directors, because indonesia is adopting a two-tier system. The companies sampled is a company registered in the Indonesia Stock Exchange (IDX).Adjusted R-squere value (0.55) shows that voluntary corporate disclosure nearly 55% depending on the independent variable is gender diversity of the board, board diversity educational backgrounds, profitability, size, liquidity and liverage of the company. Significance test showed that gender diversity and leverage are important determinants of corporate voluntary disclosure in Indonesia. On the other hand, the research also found that the variable gender diversity, provitability, size and liquidity is not strong explanatory variables to determine the extent of voluntary disclosure of company in Indonesia.